Investigating the Tradeoff Between the MMF Distortion and End Turn Length of a 2-Pole Line Start SynRM Performance - Tekgun, Didem; Cosdu, Muhammed M.; Tekgun, Burak; Alan, Irfan (Springer int Publ Ag, 2023)
Conventional 2-pole AC machine windings have long end windings and generate harmonics, which increase losses and reduce torque density. This study investigates the performance tradeoff between the level of distortion (THD) in winding magneto-motive force (MMF) and end turn length on a 2-pole line start Synchronous Reluctance Machine (LS-SynRM) machine. A two-stage approach is used, winding and geometry optimization. Various multilayer winding configurations having unevenly distributed number of turns are investigated. First, the percentage of the turns in a coil group is optimized for minimum harmonics and end turn length for all structures. Second, geometric optimization is performed on selected winding configurations. Sixteen different configurations are optimized, and Pareto optimal solutions are obtained. Later, these solutions are graded with a new score-based assessment method to quantify the quality of the results. It is concluded that the designs having lower THD in winding MMF perform better than the designs with shorter end turns in terms of efficiency and torque density.
Tekgun, Burak/0000-0003-2720-8816
Keywords: Winding Mmf Harmonics; Multi-Objective Optimization; Differential Evolution; End Winding Optimization; Reluctance Machine